Sustainability initiatives in Canadian ports. (August 2019) - Hossain, Tahazzud; Adams, Michelle; Walker, Tony R.
Abstract: Canadian ports contribute to the Canadian economy and social development. Society increasingly expects Canadian ports to balance economic growth with social and environmental impacts. In response, some Canadian ports have implemented strategic initiatives to integrate sustainability into their operations. Through participation in the Green Marine (GM) program, these ports can measure and improve their environmental performance. This study evaluated sustainability and environmental performance at 18 Canadian major ports. Twenty-five pre-defined indicators were used to identify operational trends linked to port sustainability. Annual performance reports (eight years) published by GM were analyzed to assess trends in environmental performance. All Canadian major ports participated in the GM program, but only seven proactively integrated sustainability into their operations. Sustainability initiatives included environmental policy development, environmental monitoring, proactive energy management, stakeholder engagement, incentivizing sustainability for port users, enhanced environmental reporting, and on-going research and development. All Canadian ports need to integrate sustainability and participate in GM to improve environmental performance and remain competitive in the global maritime supply chain. Graphical abstract: Image 1 Highlights: Many Canadian ports measure environmental performance via the Green Marine (GM) program. Although few Canadian ports integrate sustainability initiatives into their operations. Some Canadian ports have discrepancies between environmental performance and sustainability initiatives. All Canadian ports need to integrate sustainability and participate in GM to remain competitive.